Nutritional Status Assessment Through Subjective Global Assessment Tool Of Patients Undergoing Hemodialysis (PUSA Journal of Hospitality and Applied Sciences, 2018)
Background: Lifestyle diseases namely Diabetes Mellitus, Hyperlipidemia, Hypertension, can lead  to life threatening condition known as Chronic Kidney Disease (CKD). It is a condition in which  the kidneys are no longer able to maintain the normal composition of blood and renal function get  completely hampered. Nearly ten percent of India’s 1.24 billion people suffer from Chronic Kidney  Disease, a disease in which the kidney slowly loses function and fails. Objective: The present study  was conducted to screen dialysis patients for the prevalence of malnutrition during their stay in  hospital through a tool namely Subjective Global Assessment (SGA). Methodology: SGA is a tool  for screening malnutrition in a wide variety of health care setting. It is a valid and clinically useful  measure of protein-energy nutritional status in maintenance dialysis patients. The study was carried  out on 60 adults with minimum age of 18years. Results: Nutritional status assessments of patients on  Haemodialysis using SGA Tool were found to be moderately malnourished (89%), 10% are severely  malnourished and remaining was well nourished. Conclusion: It was concluded that the cause behind  the poor nutritional status of majority is multi-factorial. The patients irrespective of age and gender  were not able to meet their nutrient requirement as per the Guidelines for Maintenance Haemodialysis  in India. India’s CKD problems have reached epidemic proportions, thus it is suggested that emphasis  on nutrition counselling of such patients is very important to sustain a better livelihood.
Keywords: Haemodialysis; SGA Tool; Dietary Recall; Nutrition; Chronic Kidney Diseases